Spatial mapping and predictors of ever-tested for HIV in adolescent girls and young women in Ethiopia - Shimbre, Mulugeta Shegaze; Tunja, Abayneh; Bodicha, Belay Boda; Belete, Abebe Gedefaw; Hailgebereal, Samuel; Fornah, Lovel; Ma, Wei (Frontiers in Public Health, 2024)
Background: Adolescent girls and young women (AGYW) are expected to be in a healthy stage of life. However, the unique health challenges AGYW faces include unsafe sex practices and substance abuse. In Africa, Only 46.3% of AGYW are aware of their HIV status, and difficulties are underlined in HIV testing among adolescents and young people. In order to demarcate the areas with low and high HIV testing, the study aimed to map HIV ever-tested among adolescent girls and young women in Ethiopia. Methods: Secondary data analysis was conducted from the 2016 Ethiopian Demographic and Health Survey (EHDS). We conducted Spatial autocorrelation and Moran's I statistics to investigate the regional variance in HIV ever tested in AGYW. In addition, Ordinary Least Squares (OLS) regression, and then geographically weighted regression (GWR) spatial regression analyses were done to determine the predictors of being ever tested for HIV among AGYW.Results: Addis Ababa, some parts of Amhara, Dire Dawa, Gambela, and Tigray were the hotspot region and city administration for being ever-tested for HIV among AGYW. A lesser proportion of ever-tested for HIV are found in Somalia, Afar, Benshangul Gumuz, and Southern nation nationality and people regions. The spatial regression identified age 15-19 years, Muslim religion, no formal education, no knowledge about HIV, and severe stigma were identified as predictors of being ever-tested for HIV among AGYW.The proportion of ever been tested for HIV was high in Addis Ababa, some parts of the Amhara, Dire Dawa, Gambela, and Tigray. Spatial regression for factors analysis identified that AGYW aged 15-19 years, no formal education, not knowledgeable on HIV, and severe community stigma are identified as negatively affecting the proportion of being ever-tested for HIV, while Muslim religion was positively affecting the proportion of being ever tested for HIV. The governments and other stakeholders should focus on increasing HIV testing among these special groups of the population.